Understanding social inclusion: A directed content analysis - Yvonne Tan; Imaan Bayoumi; Bruce Knox; Michele Cole; Logan Jackson; Autumn Watson; Colleen M. Davison; Susan A. Bartels; Eva Purkey (PLoS ONE, 2025)
Background Social inclusion can be defined as a process that enhances opportunities for social participation, strengthens social bonds, and ensures equitable access to opportunities and decision-making. It emphasizes the interconnectedness of society and the active roles individuals play in upholding shared values and responsibilities. This study aimed to explore factors contributing to social inclusion from the perspective of families in Kingston, Ontario who self-identified as having a history of adversity and as being resilient during the COVID-19 pandemic. Methods Participants consisted of a maximum variation sample of families who demonstrated family level resilience during the COVID-19 pandemic. Focus groups and semi-structured in-depth interviews were conducted to allow participants to explore what helped or hindered their family resilience during and beyond the pandemic. Using directed content analysis, line-by-line coding of interview transcripts was conducted to explore the fit between data and an existing social inclusion framework. Results The majority of data fit meaningfully into the dimensions established in the social inclusion framework:(1) Quality Education; (2) Innovation & Technology; (3) Governmental Policies & Laws; (4) Transportation & Infrastructure; (5) Employment & Organizations; (6) Poverty & Economy; (7) Medical & Health; and (8) Community & Culture. However, we noted that some dimensions could be both sources of and barriers to social inclusion. Additionally, our study identified specific elements not discussed in the original inclusion framework, including informal education, public gathering spaces, nature, the social dimensions of poverty, and mental health care. Conclusions Participants perceived social inclusion as a facilitator of resilience. Interventions targeting the many dimensions of social inclusion must be implemented to drive positive community transformation.